(3 + 2)-Annulation of 1, 3-N, Si-tetraorganosilane reagents TsHNCH2SiBnR1R2 with arynes for efficient synthesis of 3-silaindolines. Issue 20 (31st August 2022) - Cui, Deyun; Feng, Ying; Gan, Yu; Yin, Jiaqi; Wang, Wanshu; Fan, Yu; Gao, Lu; Ke, Bowen; Song, Zhenlei
Abstract : 1, 3- N, Si -Tetraorganosilane reagents TsHNCH2 SiBnR 1 R 2 were developed as robust synthons to prepare 3-silaindolines via a Cs2 CO3 -promoted (3 + 2)-annulation reaction with arynes. Abstract : 1, 3- N, Si -Tetraorganosilane reagents TsHNCH2 SiBnR 1 R 2 were developed as robust synthons to prepare 3-silaindolines via a Cs2 CO3 -promoted (3 + 2)-annulation reaction with arynes. The annulation involved a chemoselective Si–C bond cleavage/formation sequence, where the Si–Bn bond in TsHNCH2 SiBnR 1 R 2 and the Si–Ar bond in aryl silyl triflates were cleaved, and a new Si–Ar bond together with a N–Ar bond was formed. The nitrogen and aryl moieties in the products could be further functionalized to expand the structural diversity of 3-silaindolines. The approach allowed the development of a 3-silaindoline-containing CB2 agonist, which showed a higher CNS penetration and better antinociceptive effect than its carbon analog.